Factor space for construction of pile foundations in permafrost soils - Igor Petrovich Stoyanov (Недвижимость: экономика, управление, 2024)
Factor space is a method for determining the relationship between internal and external factors affecting the construction process. Internal factors are the processes controlled by the developer or investor during the realization of a construction project. Internal factors include: planning, controlling, intensity, quality, cost and operational reliability. External factors are conditions that cannot be influenced by the developer or investor during the realization of a construction project. External factors include: natural conditions, permafrost degradation and infrastructure.